Performance and tolerance of Moringa stenopetala exposed to drought stress during germination and growth - Nadia Khater; Kenza Garah; Toufik Aliat; Nyasha J. Kavhiza; Hani S. Saudy; Karim M. Hassan; Mahmoud A. A. Ali; Mostafa Abdelkader (PLoS ONE, 2025)
Moringa stenopetala is a rapidly growing, unappreciated tree regarded as the “miracle tree” for its food, feed, and medicinal benefits. It appears to be a versatile and promising species for use under changing conditions. However, the biological response of Moringa stenopetala, a valuable but underutilized species, to drought remains unclear during its early growth stages. Therefore, the main aim of this study was to investigate the morphological, physiological, and biochemical responses of M. stenopetala seedlings to different levels of drought stress induced by PEG-6000. Four concentrations of PEG-6000 (0, 4, 8, and 12 percent) were applied to evaluate the effect of water deficit on the morphological, physiological, and biochemical characteristics of M. stenopetala . The results indicated that the water potential exhibited a statistically significant impact on the germination rate (82.5%) and the mean germination time. The osmotic potential of the PEG solution was found to have a significant impact on germination speed (93%), the kinetics of germination (39%), the germination index (102%), and the germination vigour index (91.25). The study further revealed a positive correlation between water stress and increased stem growth and root length. Concurrently, proline content exhibited a substantial decrease, directly proportional to the stress level incurred. The accumulation of soluble sugars in the leaves exhibited variation according to stress levels. Drought indices revealed that the moderate treatment of PEG gave the highest GSI (1.325), STI (1.325), MPI (0.93), and HM (0.906), indicating drought tolerance and potential regular growth under drought stress. PCA visualized the most relationships among the studied traits of Moringa under drought stress, revealing distinct groupings and key indicators of drought tolerance, where the first two principal components (PC1 and PC2) explain most data variation (83%). These conclusions emphasize the adaptive ability of Moringa under drought stress conditions, besides proving its application as a drought-resilient crop.